2017
DOI: 10.3847/1538-4357/aa6dfc
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Galactic Winds on the Angular Momentum of Disk Galaxies in the Illustris Simulation

Abstract: Observed galactic disks have specific angular momenta similar to expectations for typical dark matter halos in ΛCDM. Cosmological hydrodynamical simulations have recently reproduced this similarity in large galaxy samples by including strong galactic winds, but the exact mechanism that achieves this is not yet clear. Here we present an analysis of key aspects contributing to this relation: angular momentum selection and evolution of Lagrangian mass elements as they accrete onto dark matter halos, condense into… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 62 publications
0
52
0
Order By: Relevance
“…Therefore extra-planar gas ejected from star forming regions -such as the spiral arms -is unlikely to reach the small radii which we consider here through a fountain flow (see e.g. Fraternali & Binney 2008;Pezzulli et al 2015;DeFelippis et al 2017). Furthermore, as discussed below in Section 4.2, the residual CO velocities are inconsistent with the CO gas in the transverse dust lane moving inwards.…”
Section: Origin Of the Transverse Dust Shellmentioning
confidence: 99%
“…Therefore extra-planar gas ejected from star forming regions -such as the spiral arms -is unlikely to reach the small radii which we consider here through a fountain flow (see e.g. Fraternali & Binney 2008;Pezzulli et al 2015;DeFelippis et al 2017). Furthermore, as discussed below in Section 4.2, the residual CO velocities are inconsistent with the CO gas in the transverse dust lane moving inwards.…”
Section: Origin Of the Transverse Dust Shellmentioning
confidence: 99%
“…Early numerical simulations were able to reproduce the main predictions from this tidal torque scenario for the origin of the dark matter halo spins (Efstathiou & Jones 1979;White 1984;Barnes & Efstathiou 1987) and further confirmation may be found in the orientations of the angular momentum of nearby disk galaxies with respect to the surrounding large scale structure (Navarro et al 2004). With the advent of more sophisticated hydrodynamical simulations it also became clear that baryons undergo a much more complex evolution than previously envisioned (van den Bosch et al 2002;Abadi et al 2003;Brook et al 2011;Scannapieco et al 2012;Bryan et al 2013;Übler et al 2014;Dubois et al 2014;Teklu et al 2015;Zavala et al 2016;Zjupa & Springel 2017;DeFelippis et al 2017;Jiang et al 2018;Garrison-Kimmel et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Brook et al 2012b;Aumer et al 2013;Marinacci et al 2014;Wang et al 2015;Colín et al 2016;Grand et al 2017). The general picture now emerging from simulations is that the formation of discs is promoted because energetic feedback expels low angular momentum gas from the central regions that later re-accretes onto the galaxy, providing fuel for late-time star formation from gas with, on average, high angular momentum (Brook et al 2011(Brook et al , 2012aÜbler et al 2014;Teklu et al 2015;Zavala et al 2016;Christensen et al 2016;Agertz & Kravtsov 2016;DeFelippis et al 2017) that should be well-aligned with the disc (e.g. Sales et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In what follows, we use a tracer particle analysis (DeFelippis et al 2017) to track the history of baryonic elements found in star particles at redshift zero (described in Section 2), and classify the type of accretion based on a set of criteria described in Section 3. In Section 4, we show that, in general, nearly all of the stars formed by redshift zero contain previously wind-recycled material, to which galactic fountain flows contribute significantly.…”
Section: Introductionmentioning
confidence: 99%